Structural Analysis of Reproductive Development in Pistillate Flowers of Laurus nobilis L. - (:unkn) unknown (My University, 2013)
In Laurus nobilis L. (Lauraceae) the development of female flowers (pistillate), between floral meristem differentiation and fruit formation was inspected through histological sections and SEM techniques. The reproductive development of the female flower starts when the apical meristem converts into a floral meristem. Four tepals, four stamens and a carpel are developed from the floral meristem in turn. Filaments emerge however, anther development is arrested, and stamens become nonfunctional staminodes. The stigma is of the dry type. The solid style being short and thick consists of an epidermis, a cortex, a vascular bundle and a core of transmitting tissue composed of elongated cells. In the style a funnel-shaped zone extending from within the stigma to the stylar base is visible. The presence of high amounts of sugars and lipid substances within and around the vascular bundles are identified by histochemical techniques. The ovary contains an anatropous, bitegmic and crassinucellate ovule. Starch grains are present throughout the development of nucellar tissue. The chalazal region of nuclear endosperm forms a short haustorium. Endosperm does not exist in mature seed; the cotyledons are piled with considerably large starch grains. Idioblasts are observed in all stages of development.